Immigrant mother- languages in Eclipse High School: an analysis on language policy of the Madrid region - Solís Casco, Isabel (Revista Complutense de Educación, 2016)
European educational language policy has moved from monolingualism to the promotion of multilingualism among Europeans and to the acknowledgement of the cultural richness of the languages found in Europe. Nevertheless, not all the languages have achieved the same degree of support or acknowledgement in European educational systems. For example, neither the status of languages spoken by immigrants nor their and their presence in classrooms has increased since the first laws governing their use in educational establishments were passed in the late seventies. In this article, through a case study forming part of a larger study regarding educational language-policy undertaken in the Madrid region, the presence of immigrant mother-tongues at a secondary school and the language ideology with respect to these languages will be analyzed. Using the ethnographic method and based on an examination of the official documents at the secondary school and the language environment found there, one reaches the conclusion that the educational context is characterized by a language ideology that renders immigrant mother-tongues invisible, despite the legislation passed and the studies undertaken which have demonstrated the benefits of valuing the mother tongues of immigrants in the educational setting.